Wywiad telewizyjny na żywo. Charakterystyka gatunku - Sobczak, Barbara (Poznańskie Studia Polonistyczne, 2006)
The present book Live Television Interview. Characteristics of the Genre fits into current research in media communication. A detailed analysis of three weekly TV programmes aired by TVP (Polish Television), Gość Jedynki [Channel One Guest Star], Krakowskie Przedmieście 27 [27 Krakowskie Przedmieście], and by TVN (Independent) Kropka nad [Dotting the I’s]), allowed the author to capture specific features of this particular genre labelled, because of the raised social and political subjects and because of the kind of guests invited to the programmes, as political interview. The book shows TV interview as an interaction during which a particular text (discourse) with particular features is created. The first two chapters of the book are theoretical and describe this kind of an interview as a journalese genre (Chapter One), and as the object of linguistic research (Chapter Two). Chapter Three examines the current position of the television interview. The following elements are analyzed: time, place, subject, the objective of the interview, its participants and their communication roles in the programmes. Chapter Four includes a description of the internal ordering of the television interview (consecutive stages of the interview, the ways of introducing a subject, the pairs question-answer), a description of its individual elements, their function and mutual relations as well as a description of the features of the language used, taking into account the unique character of such a communication situation as one of a live TV broadcast of a conversation on a given subject. Particular emphasis is put to the analysis of the pairs question-answer and to disruption of the communicative process resulting from breaking the rules of conversation or vocal abuse, including speaking too loudly, using improper pitch, or using inappropriate breathing patterns. The adopted interactionist viewpoint in this study of the television interview made it possible to include in the analysis not only linguistic means but also extra-linguistic, nonverbal features such as elements of proxemic, kinesic and cultural codes.
Live Television Interview. Characteristics of the Genre
Keywords: wywiad telewizyjny; rozmowa; gatunek dziennikarski; pytanie; wywiad na żywo; struktura wywiadu; komunikowanie masowe; television interview; genre; question; media communication; live interview